Cognitive Behavioral Insomnia Therapy for Those With Insomnia and Depression: A Randomized Controlled Clinical Trial - Carney, Colleen E. (Sleep, 2017)
STUDY OBJECTIVE: To compare cognitive behavioral therapy for insomnia (CBT-I) + antidepressant medication (AD) against treatments that target solely depression or solely insomnia. DESIGN: A blinded, randomized split-plot experimental study. SETTING: Two urban academic clinical centers. PARTICIPANTS: 107 participants (68% female, mean age 42 ± 11) with major depressive disorder and insomnia. INTERVENTIONS: Randomization was to one of three groups: antidepressant (AD; escitalopram) + CBT-I (4 sessions), CBT-I + placebo pill, or AD + 4-session sleep hygiene control (SH). MEASUREMENTS AND RESULTS: Subjective sleep was assessed via 2 weeks of daily sleep diaries (use of medication was covaried in all analyses); although there were no statistically significant group differences detected, all groups improved from baseline to posttreatment on subjective sleep efficiency (SE) and total wake time (TWT) and the effect sizes were large. Objective sleep was assessed via overnight polysomnographic monitoring at baseline and posttreatment; analyses revealed both CBT groups improved on TWT (p = .03), but the AD + SH group worsened. There was no statistically significant effect for PSG SE (p = .07). There was a between groups medium effect observed for the AD + SH and CBT + placebo group differences on diary TWT and both PSG variables. All groups improved significantly from baseline to posttreatment on the Hamilton Rating Scale for Depression (HAMD-17); the groups did not differ. CONCLUSIONS: Although all groups self-reported sleeping better after treatment, only the CBT-I groups improved on objective sleep, and AD + SH’s sleep worsened. This suggests that we should be treating sleep in those with depression with an effective insomnia treatment and relying on self-report obscures sleep worsening effects. All groups improved on depression, even a group with absolutely no depression-focused treatment component (CBT-I + placebo). The depression effect in CBT-I only group has been reported in other studies, suggesting that we should further investigate the antidepressant properties of CBT-I.